Servant leadership and its role in achieving job security An exploratory study of the opinions of a sample of employees in a number of private universities in the Kurdistan Region – Iraq - Tawfeeq, Karwan; Nuri Daoud, Ranaj (Humanities Journal of University of Zakho, 2022)
Abstract The research aims to identify the role of servant leadership in job security. The research problem was represented in the availability of levels of job security among employees in a number of private universities in the Kurdistan Region - Iraq, and dimensions of servant leadership style among administrative leaders in those universities. For the purpose and in order to test the research hypotheses, a sample of the private universities in the Kurdistan Region - Iraq, which are (6) universities, were chosen, and represented the research community with employees in terms of administrators and academics contracting in those universities, and the research sample consisted of (106) individuals who answered the questionnaire about their levels of agreement on the availability of servant leadership dimensions among leaders in their universities, as well as their own answers about the availability of levels of job security. The questionnaire was used as a main tool in collecting data related to the field side. The research hypotheses were tested using a set of statistical methods suitable for analysis. The research was reached a set of conclusions, the most important is the existence of a significant correlation between servant leadership and job security in the universities investigated, as well as a significant effect of the dimensions of the servant leadership represented by (helping followers to develop and succeed, generate value for society, empathy, conceptual skills, and act ethically) in job security. The impact of empowerment, as one of servant leadership dimensions, on job security not appeared. The study concluded with a set of recommendations and proposals for the universities, the research community, as well as the proposed recommendations for future researchers in the topics of servant leadership and job security.